Effects of shRNA-mediated knockdown of SPOCK1 on ovarian cancer growth and metastasis - Zhang, L-Q; Wang, Y; Zhang, L (Cellular and Molecular Biology, 2015)
Ovarian cancer is one of the three most common gynecological malignant tumors. The mortality rate of ovarian cancer is high because of the insidious disease onset and the lack of effective methods for early diagnosis. In this study, we assessed the potential of SPOCK1 as a significant biomarker for ovarian cancer development. We determined that the expression of SPOCK1 was evidently high in ovarian cancer tissues and the cell lines OVCAR3 and SKOV3. The knockdown of SPOCK1 by specific shRNA significantly inhibited cell proliferation and colony formation in both OVCAR3 and SKOC3 cells. In a xenograft model of ovarian cancer, the mice implanted with SPOCK1 knockdown SKOV3 cells exhibited a slower tumor growth rate. The dissected tumors also weighed less in the SPOCK1-depleted mice group. Furthermore, the knockdown of SPOCK1 evidently inhibited the wound recovery process. Concomitantly, cell migration was inhibited by up to 67% after the knockdown of SPOCK1 in OVCAR3 cells and 75% in SKOV3 cells. Invasion capability also decreased by up to 80% in OVCAR3 cells and 83% in SKOV3 cells after SPOCK1 knockdown. Moreover, the knockdown of SPOCK1 caused a decrease of its known target, i.e., matrix metalloproteinase-2. Interestingly, it also reduced phosphorylated ERK and AKT. These data suggest that SPOCK1 is a potential biomarker that promotes ovarian cancer growth and metastasis. The biological behavior of SPOCK1 in ovarian cancer may be related to the ERK and AKT signaling pathways.